Penggunaan Gamifikasi Dalam Proses Pembelajaran Jarak Jauh Untuk Meningkatkan Motivasi dan Literasi Digital Siswa - Nainggolan, Grecia Angelika; Hafidza, Nadhira; Br Bangun, Yosinda Naberti; Simorangkir, Chalerina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Gamification has become one of the innovative methods in education, especially in the context of distance learning (PJJ). In this article, we explore the application of gamification in the learning process to improve students' learning motivation and digital literacy. This study was conducted by researchers from the Faculty of Education, State University of Medan, with data collected from various trusted sources and the results of mini-research on Jalan Elang Ujung Perumnas Mandala Medan. Gamification has emerged as an innovative method in education, especially in the context of distance learning (PJJ). The study conducted by researchers from the Education Science, State University of Medan, explores the application of gamification to improve students' learning motivation and digital literacy. Gamification refers to the use of game elements in non-game contexts to increase engagement and motivation. In education, this can include the use of points, badges, and challenges that encourage students to participate more actively in the learning process. The results of the study showed that the application of gamification can significantly increase students' learning motivation. The combination of good digital literacy and high reading interest contributed to this increase in motivation, with digital literacy having an influence of 46.8% and reading interest of 46.2%. Students who have digital literacy skills tend to be more confident in learning new material, while increasing interest in reading can be encouraged through gamification which makes the learning process more interesting and interactive. Thus, the application of gamification in education has proven to be effective in creating a dynamic and interesting learning environment, so that students are motivated to be actively involved in the learning process.